2020
DOI: 10.21203/rs.3.rs-41883/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association Between Glucose Variability And Postoperative Delirium In Acute Aortic Dissection Patients: An Observational Study

Abstract: Background: Blood glucose variability is associated with poor prognosis after cardiac surgery, but the relationship between glucose variability and postoperative delirium in patients with acute aortic dissection is unclear. The study aims to investigate the association of blood glucose variability with postoperative delirium in acute aortic dissection patients.Methods: We prospectively analyzed 257 patients including 103 patients with delirium. The patients were divided into two groups according to whether del… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…In a clinical observational study, T2DM reduced the clinical complications and mortality in Stanford type B aortic dissection after thoracic endovascular aortic repair during 3-year follow up [18]. While, Lin YJ et al were found that glucose variability was associated with the incidence of postoperative delirium in acute aortic dissection patients [19]. For T2DM, there was not signi cant difference between two groups in our study.…”
Section: Discussioncontrasting
confidence: 57%
“…In a clinical observational study, T2DM reduced the clinical complications and mortality in Stanford type B aortic dissection after thoracic endovascular aortic repair during 3-year follow up [18]. While, Lin YJ et al were found that glucose variability was associated with the incidence of postoperative delirium in acute aortic dissection patients [19]. For T2DM, there was not signi cant difference between two groups in our study.…”
Section: Discussioncontrasting
confidence: 57%
“…Preoperative HbA1C and random blood glucose were associated with PACU delirium in our study. Lin et al similarly found that high glycaemic variability increases the risk of PACU delirium in acute aortic dissection patients, 23 while Heymann et al also found that patients with hyperactive delirium had higher mean blood glucose than the non-hyperactive delirium patients. 24 As a simple carbohydrate, the effect of glucose on the body is significant.…”
Section: Discussionmentioning
confidence: 98%
“…AAAD is a clinical emergency, in which the pathophysiological change results in inducing intensive stress responses that can cause damage to the stability of the body's intracellular environment and finally to glycometabolism disorders of patients. 11) Our previous study 12) uncovered that high glycemic variability increases the risk of postoperative delirium. However, the influence of admission hyperglycemia on patients with AAAD has not yet been reported.…”
mentioning
confidence: 99%